1999
DOI: 10.1002/(sici)1097-4636(19990905)46:3<418::aid-jbm15>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunohistochemical studies of membranes of deacetylated chitin derivatives implanted over rat calvaria

Abstract: Membranes made of 65, 70, 80, 94, and 100% deacetylated chitin (chitosan) were implanted subperiosteally over the calvaria of 100 rats. Reactions were studied at 1, 2, 4, and 8 weeks after implantation. Membranes prepared with 65, 70, and 80% deacetylated chitin initially elicited marked inflammatory reactions that subsided in time with granulation tissue formation and osteogenesis. Osteocalcin-positive cells were detected immunohistochemically in the granulation tissue. On the other hand, membranes made of 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 14 publications
3
39
2
3
Order By: Relevance
“…Previous studies have shown that chitosan demonstrates chemotactic potential in vitro and in vivo . 2527 There are many studies, which showed minimal inflammatory response of chitosan, 2829 but there also exists many studies which show that chitosan could lead to high degree of inflammatory infiltrates 3031 and that reaction could last for long periods. 32 But in our case, for chitosan-TPP and chitosan-TPP-BMP-7 microparticles fabricated by coacervation technique, we observed minor inflammatory response at week 6, which reduced by 12 weeks period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chitosan demonstrates chemotactic potential in vitro and in vivo . 2527 There are many studies, which showed minimal inflammatory response of chitosan, 2829 but there also exists many studies which show that chitosan could lead to high degree of inflammatory infiltrates 3031 and that reaction could last for long periods. 32 But in our case, for chitosan-TPP and chitosan-TPP-BMP-7 microparticles fabricated by coacervation technique, we observed minor inflammatory response at week 6, which reduced by 12 weeks period.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan degree of deacetylation (DDA) has often been cited as an important parameter that determines many physiochemical and biological properties of chitosans such as crystallinity, hydrophilicity, degradataion and cell response [6,7,8,9,10,11]. For example, Freier et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hidaka et al . [10] reported that chitosan membranes between 65 and 80% DDA elicited marked inflammatory reactions that subsided in time with degradation of the films, granulation tissue formation, and osteogensis while membranes made of 94% DDA chitosan showed minimal degradation, mild inflammation and minimal osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Hidaka [18] reported that a 94% DDA chitosan membranes gave minimal film degradation, mild inflammatory reaction and minimal osteogenesis while between 65 to 80% gave the opposite response.This effect is more or less in line to our survival rate results for all three different cell lines ( Figure) that the higher the degree of de-acetylation the more the survival rate and that 87% de-acetylation actually improved the cell survival rate to above 100%.…”
Section: Discussionmentioning
confidence: 99%